Join rate improvements in P2P live streaming based on topological aspects during flash crowds - Miguel, Eliseu César; Coelho, Fernando C. S.; Morgan, Bruno; Junior, Murilo Calado; Cunha, Ítalo; Campos, Sérgio (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
In P2P networks peers share content in a topological overlay above the physical network. This is fundamental to network's performance. However, the simultaneous arrival of many peers, known as flash crowd, can affect network topology and disrupt content transmission. Current studies frequently separate flash crowd from topology arrangement techniques. In this work, we set topological partnership restrictions to preserve the existing mesh during a flash crowd. Using a parallel network technique, incoming peers are isolated in sub channels to avoid new relationship interference between newcomers and existing peers. This is particularly important because incoming free riders may affect existing cooperative peers significantly. In our experiments, we show that this restriction has allowed the transmission to remain unaffected in the presence of a flash crowd six times greater than would have been possible without the proposed technique.